Analisis Pengaruh Trendlines Dan Consumer Involvement Pada Brand Engagement Sebagai Variabel Mediasi Terhadap Purchase Intention Produk Skintific - Mahgaraini, Petty Christin; Irmawati, Irmawati (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
The development of cosmetics in today's era has become a necessity that cannot be underestimated anymore. “According to its use, cosmetics are divided into two, namely cosmetics used to care for and maintain the cleanliness of facial skin, often known as Skincare, and cosmetics used to apply makeup and cover deficiencies in facial skin, often known as Make up” (A. Putri, 2017). The population in this study is students of the University of Muhammadiyah Surakarta. The sampling technique in this study is non probability sampling. The sampling technique used is purposive sampling where this technique is used to determine the research sample with certain considerations or criteria that have the purpose that the data obtained is representative data.